Growth of four types of Capsicum spp. in substrates under a protected environment - Ruiz-Espinoza, Francisco Higinio; Rodríguez-Ortiz, Juan Carlos; Beltrán-Morales, Félix Alfredo; Carballo-Méndez, Fernando de Jesús (Revista de la Facultad de Agronomía de la Universidad del Zulia, 2021)
Plant growth depends on environmental conditions, management conditions and soil conditions, which is why in this research we evaluated the growth of chili peppers in a sand-based substrate, under a protected environment. The treatments evaluated were: 1) soil (control), 2) sand, 3) sand-perlite (4:1) and 4) sand-perlite (1.5:1), which were established under a completely randomized design with six replications. The species used were Capsicum annuum L. Hungarian, serrano and jalapeño types, and Capsicum pubescens Ruiz & Pav. apple type. The sand-perlite mixtures benefited the growth of the chili peppers, with respect to soil and sand. Therefore, sand-perlite mixtures should be considered as an alternative to produce chili peppers in containers.